Instilling Family Values among Students through the Tradition of Ro'an (Community Service) in Islamic Boarding Schools - Yuli Choirul Umah; Qurotul A’yun; Nur Iftitahul Husniyah; Matnur Ritonga; Djamaluddin Perawironegoro (STAI Miftahul Ula Nganjuk, 2025)
This study aims to describe the implementation of the Ro'an (mutual cooperation) tradition at the Sunan Kalijaga Islamic Boarding School in Patianrowo, Nganjuk, to explain efforts to instill family values among students through this tradition, and to analyze the outcomes of these efforts. A qualitative approach was employed, based on interpretive philosophy, to gather in-depth insights. The research findings reveal that the Ro'an tradition is effectively conducted, fostering strong social bonds among students as they work together with sincerity and cooperation. This tradition significantly contributes to nurturing a sense of family among the students, strengthening their social relationships and communal spirit.